2 Suitability of univentricular patients for cardiac resynchronisation therapy. (28th April 2017) - Gubran, C; Demetriades, P; Clift, P; Thorne, S; Bowater, S; Marshall, H; Bono, J de; Hudsmith, L
Abstract : Introduction: In 2014 the Paediatric And Congenital Electrophysiology Society (PACES) and Heart Rhythm Society (HRS) published expert consensus statement regarding arrhythmia management in congenital heart disease, including Cardiac Resynchronisation Therapy (CRT) indications for adult congenital heart disease (ACHD) patients. These guidelines recommend CRT in univentricular hearts for those who have an impaired ventricle (EF ≤35%) with QRSd ≥150 ms, ventricular dilatation and NYHA II-IV[IIa, C]. Methods: Retrospective analysis for EF, QRSd and NYHA status, from 211 patients with a Fontan circulation under specialist ACHD follow-up. Results: Univentricular functional data was available for 94% (198, 84 CMR and 114 echo). 10 (5%) patients had EF ≤35%. QRSd was available for 91% (193). 5 (3%) had QRSd≥150 ms. 2 patients were identified with both EF ≤35% and QRSd ≥150 ms, fulfilling indications for CRT. One patient was NYHA IV, tricuspid atresia with an atriopulmonary fontan and subsequent conversion to total cavopulmonary circulation (TCPC). The second patient (NYHA II) had right atrial isomerism with pulmonary atresia and an unfenestrated TCPC. Conclusions: If recent HRS CRT guidelines are applied to this large adult Fontan population there are very few candidates for CRT. Guidelines should be interpreted with caution. In virtually all cases, CRT device implantation in the adult Fontan will require a cardiac surgical approach associated with significant morbidity and mortality. The decision to implant CRT in Fontan patients is therefore complex and requires discussion in a combined ACHD electrophysiology MDT with careful consideration of patient anatomy and previous surgery